Multiaspect Sustainability Analysis of Household-Scale Coconut Sugar Enterprises in Besan Village, Klungkung - Putu Oktavia Kusumadewi; Ketut Budi Susrusa; Ni Luh Prima Kemala Dewi (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2025)
Coconut sugar production represents a vital component of the rural economic structure in Besan Village, Dawan District, Klungkung Regency. However, the sustainability of this household-based enterprise faces multifaceted challenges related to economic, social, environmental, institutional, and technological aspects. This study aims to assess the current sustainability status, identify the most influential attributes, and formulate improvement scenarios for household-scale coconut sugar enterprises. A mixed-methods approach was employed, utilizing primary data collected through questionnaires distributed to 15 key informants, supported by relevant secondary data. The data were analyzed using the Multiaspect Sustainability Analysis (MSA) method.The application of MSA in this study offers a holistic evaluative framework for assessing the sustainability of small-scale, local agro-industries—an approach that has rarely been applied to traditional production systems such as coconut sugar. The results show that the current sustainability level falls into the low category, with a score of 44.56. Sensitive attributes include environmental pollution, financial record-keeping, social security, access to financing, and digital marketing adoption. The first improvement scenario raised the score to 70.51, indicating a sustainable status, while the second scenario achieved 88.47, categorized as very sustainable.These findings provide empirical foundations for policy formulation and development strategies to strengthen the long-term sustainability of household-based coconut sugar enterprises in rural areas.